East Asia Regional integration: A concern on economics and human development - Duasa, Jarita (2014)
The current study attempts to dwell on the issue whether the East Asian countries should adopt a more structured or institutionalized approach in their efforts toward greater regional economic integration, that is, through „human development‟ which covers economic, social, health and environmental conditions. The analysis is done by testing the level of convergence or divergence of human development components (economic, social, health and environmental conditions) within members of ASEAN(6+CMLV), Japan, Korea and China. The tests of convergence or divergence determine suitable countries to form the proposed integration base on the human development indicators. A common method used is augmented Dickey-Fuller (ADF) linear test of stationarity. The second method adopted is the Kapetanois et al. (2003), KSS, non-linear stationary test which enables to detect the presence of non-stationarity against non-linearity. The study finds possible integration among the countries in studies based on the human development indicators.